A new friend - Pearl, Alexa, 1967- (Pearl, Alexa, 1967- Tales of Sasha, 2017)
When Sasha befriends a fun-loving flying horse named Kimani, her best friend Wyatt is jealous, and Kimani is wary of Wyatt because he does not have wings.